Analysis of Personal Competency of Driving Teachers in Managing Learning in Elementary Schools - Utami, Rina; musafir, musafir; muhajirin, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to analyze and describe the personality competencies of driving teachers in managing classroom learning through their personality competencies in elementary schools. This research is qualitative research, using descriptive methods, data collection techniques in this research, namely, observation, interviews and documentation. Results research shows that the competence of driving teachers in elementary schools here is with good personality competence in mastering and understanding their personality competencies, a strong and stable personality can be seen through Firstly, a strong and stable personality, such as, provoking students to be able to ask questions, driving teachers guiding students to carry out creative actions, driving teachers being role models for students, driving teachers being objective. Second, the mature personality referred to here, the driving teacher is professional, the driving teacher puts students above everything else. Third, a wise and wise personality is meant here, the driving teacher gives students motivation, the driving teacher forms students' disciplinary attitudes, the driving teacher is able to be wise in every situation and condition. Fourth, a responsible and authoritative personality, what is meant here is that the driving teacher provides the best example to students, takes responsibility for students, fosters an attitude of respect and responsibility. Fifth, have morals, that is, teachers who encourage students to teach morals and obey good rules.